The Correlation Between Classroom Management and Student Interests - Muli Umiaty Noer; Sri Suci Utami; Abdollah Abdollah (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
The research aimed were to find out the correlation between classroom management and student’s interest. This research uses quantitative with survey method that apply correlation technique there are two variable in this research, namely dependent variable and independent variable. The independent variable is classroom management while dependent variable is students interest the population of this research as two classes of ABA UMI year 2016-2017. The samples of this research are 20 respondents taken through purposive sampling technique . in analysis the data of this research, the write used ( Correlation ). The findings of this study shows that there is any significant correlation between classroom management and student’s interest at the second grade of social class ABA UMI. This is proved by the value of the pearson product moment is -025 it means the correlation. And classroom management and student’s interest is weak. And correlation classroom management has an important role in learning process because if there is in classroom management the student’s will not be interest in learning process.